Taxation and Economic Growth in Colombia - Roberto Steiner (Inter-American Development Bank (IDB), 2014)
This Working Paper assesses the impact on investment of a reduction in corporate taxes and the impact on employment, labor formality, and growth of a reduction in non-wage labor costs in Colombia. First, and following Hall and Jorgensen (1967), we estimate an investment function, which depends on the user cost of capital, one of whose determinants is the corporate tax rate. Our estimations suggest that a reduction of the corporate tax rate from 33 to 23 percent–as originally envisioned by the government in early 2012, but finally not included in the reform submitted to Congress–has very different short and long-term effects on investment in machinery and equipment. While the user cost of capital declines 0.9 percent, investment (excluding the oil and mining sector) increases on impact only 28 bps in relation to GDP, an increase that does not compensate the fiscal cost incurred. In the long term, however, it is likely that the significant boost in investment (of around 5 percent of GDP) makes such a policy intervention fiscally sustainable. Second, using a computable general equilibrium model calibrated for Colombia, we estimate that the reduction of the "pure tax" component of non-wage labor costs approved in late 2012 is associated with a 0.5 percent increase in overall employment and, more importantly, with a 1.4 percent increase in formal sector employment. Our estimations indicate that this is achieved at no fiscal cost since government revenue increases as a result of higher output and employment.
hdl:11319/6379
Keywords: D58; E22; H30; J32; O5; 330; Computable general equilibrium models; Investment; User cost of capital; Corporate taxation; Non-wage labor costs